Composite additive for vanadium electrolyte and preparation method thereof
By using a composite additive composed of fluorine-containing compounds and surfactants in the vanadium battery electrolyte, the precipitation and crystallization problems that vanadium batteries occur when increasing the vanadium ion concentration are solved, and the electrochemical activity and performance are significantly improved.
Patent Information
- Application Number
- CN202411805829.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
AI Technical Summary
When vanadium batteries increase the concentration of vanadium ion to enhance energy density and broaden the temperature application range, precipitation of positive electrode vanadium ions and crystallization of negative electrode vanadium ions are prone to decline in electrochemical performance.
A composite additive for vanadium electrolyte is used, which consists of fluorine-containing compounds, oxygen-containing acids, and their salts and surfactants. It is used in the positive and negative electrode electrolytes of vanadium batteries to inhibit the precipitation and crystallization of vanadium and improve electrochemical activity.
It effectively inhibits the high-temperature precipitation and low-temperature crystallization of vanadium ions, improves the performance and efficiency of vanadium batteries, and maintains the temperature stability and electrochemical activity of the electrolyte.
Smart Images

Figure CN119674157A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of vanadium batteries, and in particular to a composite additive for vanadium electrolyte and a preparation method thereof. Background Art
[0002] All-vanadium liquid flow battery (hereinafter referred to as vanadium battery) is a liquid redox battery that uses metal vanadium ions as the active medium. It has won wide attention in the market in the field of long-term energy storage for its ultra-long cycle life, excellent safety, flexible design, and wide range of application scenarios. Vanadium electrolyte is the energy storage medium of vanadium battery, a key component, and plays a vital role in the performance and service life of vanadium battery.
[0003] Compared with other energy storage technologies such as lithium batteries, vanadium batteries have a lower energy density and a narrow applicable temperature range. Therefore, increasing the concentration of vanadium ions, improving the energy density of vanadium batteries, and widening the applicable temperature range are hot research directions for improving the performance of vanadium batteries. However, the increase in vanadium ion concentration is more likely to lead to the precipitation of vanadium ions at the positive electrode and the crystallization of vanadium ions at the negative electrode, while narrowing the applicable temperature range. As the vanadium concentration increases, the electrolyte concentration increases, the fluidity decreases, and the contact between the active substance and the active sites of the electrode decreases, resulting in weakened electrochemical performance. From a macroscopic perspective, although the concentration of vanadium electrolyte is increased, the applicable temperature range is shortened, and the mass-to-energy ratio decreases. Therefore, how to inhibit the precipitation and crystallization of vanadium and improve the electrochemical activity of vanadium batteries has become an urgent problem to be solved. Summary of the invention
[0004] The present application provides a composite additive for vanadium electrolyte and a preparation method thereof. The composite additive is applied to the electrolyte of a vanadium battery, can inhibit the precipitation and crystallization of vanadium, and can improve the electrochemical activity of the vanadium battery.
[0005] In order to achieve the above objectives, this application adopts the following technical solutions:
[0006] In a first aspect of the embodiment of the present application, a composite additive for a vanadium electrolyte is provided, which is applied to the electrolyte of a vanadium battery, wherein the electrolyte is a positive electrode electrolyte and a negative electrode electrolyte, and the composite additive comprises:
[0007] A mixture formed by a first component and a second component, wherein the first component includes at least one of a fluorine-containing compound, an oxygen-containing acid and an oxygen-containing acid salt, and the second component is a surfactant.
[0008] As a possible implementation, the first component includes: at least one of potassium perfluorobutylsulfonate, perfluorobutylsulfonyl fluoride, perfluorobutylsulfonamide, ammonium perfluorobutylsulfonate, ammonium fluoride, ammonium bifluoride, ammonium sulfate, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid and sulfuric acid.
[0009] As a possible implementation, the second component includes: an aqueous solution formed by at least one of polyoxyethylene esters, sorbitan esters, glycerol fatty acid esters, alkyl phosphates, ethanol, ethylene glycol, isopropanol, propylene glycol, and glycerol.
[0010] As a possible implementation, the mass concentration of the second component in the composite additive is 4%-10%.
[0011] As a possible implementation manner, the added amount of the composite additive is 0.5%-2% of the volume of the electrolyte.
[0012] As a possible implementation, the vanadium ion concentration in the electrolyte is 1.7-3.0 mol / L.
[0013] As a possible implementation, the electrolyte supports a proton concentration of the electrolyte of 8.0-10.0 mol / L.
[0014] As a possible implementation method, the electrolyte V 3+ and V 4+ The concentration ratio is 1:1.
[0015] In a second aspect of the embodiment of the present application, a method for preparing a composite additive for a vanadium electrolyte is provided, which is used to prepare the composite additive for a vanadium electrolyte in the first aspect of the embodiment of the present application, and the method comprises:
[0016] The mixture is prepared by adding 150-850 g of the first component to each liter of the second component and mixing;
[0017] Wherein, the first component comprises: at least one of a fluorine-containing compound, an oxygen-containing acid and an oxygen-containing acid salt, and the second component is a surfactant.
[0018] The beneficial effects brought by the technical solution provided by the embodiment of the present application include at least:
[0019] The embodiment of the present application provides a composite additive for vanadium electrolyte and a preparation method thereof. The composite additive is used in the positive electrolyte and negative electrolyte of a vanadium battery. The composite additive comprises: a mixture formed by a first component and a second component, wherein the first component comprises: at least one of a fluorine-containing compound, an oxygen-containing acid and an oxygen-containing acid salt, and the second component is a surfactant. Among them, the fluorine-containing compound, oxygen-containing acid and oxygen-containing acid salt in the first component can effectively reduce the viscosity of the electrolyte, improve the wettability of the electrode surface, promote the electrode reaction, and at the same time inhibit the high-temperature precipitation and low-temperature crystallization of vanadium ions, effectively improving the performance and efficiency of the vanadium battery. The surfactant of the second component has multiple functions such as reducing interfacial tension and enhancing the flexibility of the interfacial film, and can promote and stabilize the mixing with the first component to form a microemulsion or suspension, and enhance the dispersibility. At the same time, it can reduce the electrode interface resistance, improve the electrocatalytic ability of the electrode, and can also complex with vanadium ions to inhibit precipitation and crystallization. The composite additive can maintain the temperature stability and electrochemical activity of the positive and negative electrolytes of the vanadium battery. The composite additive can be used as a common additive for the positive and negative electrolytes at the same time, and there is no cross-contamination of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A test curve diagram of the cycle performance of a vanadium electrolyte provided in an embodiment of the present application. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0022] In the following, the terms "first" and "second" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present disclosure, unless otherwise specified, "plurality" means two or more.
[0023] Additionally, the use of “based on” or “according to” is meant to be open and inclusive, as a process, step, calculation, or other action “based on” or “according to” one or more conditions or values may, in practice, be based on additional conditions or beyond values.
[0024] All-vanadium liquid flow battery (hereinafter referred to as "vanadium battery") is a liquid redox battery that uses metal vanadium ions as the active medium. It has won wide market attention in the field of long-term energy storage with its ultra-long cycle life, excellent safety, flexible design, and a wide range of application scenarios.
[0025] During the operation of the vanadium battery, the active materials of the positive and negative electrodes are stored in their own tanks. When the battery is charged and discharged, the positive and negative electrolytes circulate between their own tanks and half-cells under the action of an external pump, and undergo redox reactions on both sides of the ion exchange membrane. This process forms V 5+ / V 4+ and V 3+ / V 2+ Redox couples enable efficient conversion between chemical energy and electrical energy.
[0026] The electrolyte is the energy storage medium of vanadium batteries and a key component. It plays a vital role in the performance and service life of vanadium batteries. At present, the commonly used supporting electrolyte of vanadium electrolyte is sulfuric acid. Due to the low solubility of vanadium ions in sulfuric acid medium, its concentration is low. At the same time, the pentavalent vanadium ions in the positive electrode electrolyte are easy to precipitate at high temperatures, and the divalent and trivalent vanadium ions in the negative electrode electrolyte are easy to crystallize at low temperatures. This will not only reduce the battery capacity, but also cause flow blockage, making the battery system unable to operate normally.
[0027] At present, the vanadium electrolyte used in large areas of industry usually has a vanadium ion concentration of 1.6-1.7 mol / L and an operating temperature range of 5-40°C. Compared with other energy storage technologies such as lithium batteries, vanadium batteries have a lower energy density and a narrow applicable temperature range. Therefore, increasing the concentration of vanadium ions, improving the energy density of vanadium batteries, and broadening the applicable temperature range are hot research directions for improving the performance of vanadium batteries. However, the increase in vanadium ion concentration is more likely to lead to the precipitation of vanadium ions at the positive electrode and the crystallization of vanadium ions at the negative electrode, while narrowing the applicable temperature range. As the vanadium concentration increases, the electrolyte concentration increases, the fluidity decreases, and the contact between the active material and the active sites of the electrode decreases, resulting in a weakening of the electrochemical performance. From a macroscopic perspective, although the concentration of the vanadium electrolyte is increased, the applicable temperature range is shortened, and the mass-to-energy ratio decreases. Therefore, how to inhibit the precipitation and crystallization of vanadium and improve the electrochemical activity of vanadium batteries has become an urgent problem to be solved.
[0028] In order to solve the above problems, the embodiment of the present application provides a composite additive for vanadium electrolyte, which is applied to the electrolyte of vanadium battery, wherein the electrolyte is a positive electrode electrolyte and a negative electrode electrolyte, and the composite additive comprises:
[0029] A mixture formed by a first component and a second component, wherein the first component includes at least one of a fluorine-containing compound, an oxygen-containing acid and an oxygen-containing acid salt, and the second component is a surfactant.
[0030] Optionally, the first component is a compound or mixture formed by at least one of potassium perfluorobutylsulfonate, perfluorobutylsulfonyl fluoride, perfluorobutylsulfonamide, ammonium perfluorobutylsulfonate, ammonium fluoride, ammonium bifluoride, ammonium sulfate, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid and sulfuric acid.
[0031] The second component is prepared from at least one of polyoxyethylene ester, sorbitan ester, glycerol fatty acid ester, alkyl phosphate, ethanol, ethylene glycol, propylene glycol, glycerol, isopropanol and water. The mass concentration of the second component in the composite additive is 4%-10%.
[0032] The composite additive is a solution, microemulsion or suspension composed of a first component and a second component. The composite additive is prepared by adding 150-850 g of the first component per liter of the second component and mixing by heating, stirring or ultrasound.
[0033] It should be noted that the composite additive prepared by the above method is a high-concentration concentrated solution, which can be diluted with deionized water before use according to actual needs.
[0034] Optionally, the amount of the composite additive added is 0.5%-2% of the volume of the electrolyte. The vanadium ion concentration in the electrolyte is 1.7-3.0 mol / L. The proton concentration of the electrolyte supporting the electrolyte is 8.0-10.0 mol / L. 3+ and V 4+ The concentration ratio is 1:1.
[0035] The embodiment of the present application provides a composite additive for vanadium electrolyte, which is used in the positive electrolyte and negative electrolyte of vanadium battery. The composite additive includes: a mixture formed by a first component and a second component, wherein the first component includes: at least one of a fluorine-containing compound, an oxygen-containing acid and an oxygen-containing acid salt, and the second component is a surfactant. Among them, the fluorine-containing compound, oxygen-containing acid and oxygen-containing acid salt in the first component can effectively reduce the viscosity of the electrolyte, improve the wettability of the electrode surface, promote the electrode reaction, and at the same time inhibit the high-temperature precipitation and low-temperature crystallization of vanadium ions, effectively improving the performance and efficiency of vanadium battery. The surfactant of the second component has multiple functions such as reducing interfacial tension and enhancing the flexibility of the interfacial film, and can promote and stabilize the mixing with the first component to form a microemulsion or suspension, and enhance the dispersibility. At the same time, it can reduce the electrode interface resistance, improve the electrocatalytic ability of the electrode, and can also complex with vanadium ions to inhibit precipitation and crystallization. The composite additive can maintain the temperature stability and electrochemical activity of the positive and negative electrolytes of the vanadium battery. The composite additive can be used as a common additive for the positive and negative electrolytes at the same time, and there is no cross contamination of the electrolyte.
[0036] Composite additives for vanadium electrolytes provided based on the above embodiments. The present application also provides some specific embodiments and comparative examples. The following embodiments describe the technical scheme of the present application in more detail, and these embodiments are only used for illustrative purposes, because it is obvious to those skilled in the art to make various modifications and changes within the scope of the disclosure of the present application. The reagents used in the embodiments can be obtained by commercial purchase or synthesized according to conventional methods, and can be used directly without further treatment, and the instruments and devices used in the embodiments can be obtained by commercial purchase.
[0037] Example 1: Preparation of vanadium electrolyte with a total vanadium concentration of 2.10 mol / L, V 3+ and V 4+ The concentration ratio is 1:1, and the proton concentration is 9.0 mol / L. Take the vanadium electrolyte with equal volume of positive and negative electrodes for charge and discharge test. The constant current charge cut-off voltage is 1.7V, the constant current discharge cut-off voltage is 0.6V, and the current density is 40mA·cm -2 , after 100 charge and discharge cycles, the coulomb efficiency of the vanadium electrolyte remained at 95%, the energy efficiency remained at 86%, the voltage efficiency remained at 91%, and the capacity retention rate was 35%. Take equal volumes of vanadium electrolyte for the positive and negative electrodes, charge at a constant current until the cut-off voltage is 1.8V, and stop electrolysis. Take 20ml of the positive electrode vanadium electrolyte, seal it and store it at 40℃. Precipitation occurs after 3 days. Take 20ml of the negative electrode vanadium electrolyte, seal it under nitrogen protection and store it at 5℃. Precipitation occurs after 2 days.
[0038] Example 2: Preparation of vanadium electrolyte with a total vanadium concentration of 2.10 mol / L, V 3+ and V4+ The concentration ratio is 1:1, and the proton concentration is 9.0 mol / L. 100 ml of 1# composite additive for vanadium electrolyte is prepared, wherein the first component is composed of 15 g of ammonium perfluorobutyl sulfonate, 20 g of ammonium sulfate, and 20 g of phosphoric acid, which are mixed to form a mixture; the second component is composed of 3.5 ml of polyoxyethylene sorbitan monooleate, 3.5 ml of ethanol, and 70 ml of deionized water, which are stirred with a magnetic stirrer for 20 minutes; then the first component and the second component are ultrasonically mixed at room temperature for 20 minutes, stopped, and the volume is fixed to 100 ml with deionized water, and then ultrasonically mixed at room temperature for 10 minutes, and then taken out and sealed for storage. The added volume of 1# composite additive in the positive and negative vanadium electrolytes is 1%. Take the electrolyte for vanadium batteries with equal volumes of positive and negative electrodes for charge and discharge tests. The constant current charge cut-off voltage is 1.7V, the constant current discharge cut-off voltage is 0.6V, and the current density is 40mA·cm -2 , after 100 charge and discharge cycles, the electrolyte coulomb efficiency remained at 96%, the energy efficiency remained at 86%, the voltage efficiency remained at 90%, and the capacity retention rate was 54%. According to the stability test steps of Example 1, after charging, 20 ml of the positive electrode electrolyte was sealed and stored at 40°C, and precipitation occurred after 12 days. 20 ml of the negative electrode electrolyte was sealed under nitrogen protection and stored at 5°C, and precipitation occurred after 7 days.
[0039] Example 3: Preparation of vanadium electrolyte with a total vanadium concentration of 2.10 mol / L, V 3+ and V 4+ The concentration ratio is 1:1, and the proton concentration is 9.0 mol / L. 100 ml of 2# composite additive for vanadium electrolyte is prepared, wherein the first component is composed of 30 g of ammonium perfluorobutyl sulfonate, 20 g of diammonium hydrogen phosphate, and 20 g of sulfuric acid, which are mixed to form a mixture; the second component is composed of 7.0 ml of polyoxyethylene sorbitan monooleate, 5.0 ml of propylene glycol, and 60 ml of deionized water, which are stirred with a magnetic stirrer for 20 minutes; then the first component and the second component are ultrasonically mixed at room temperature for 20 minutes, stopped, and the volume is adjusted to 100 ml with deionized water, and then ultrasonically mixed at room temperature for 10 minutes, and then taken out and sealed for storage. The added volume of 2# composite additive in the positive and negative vanadium electrolytes is 1%. Take the electrolyte for vanadium batteries with equal volumes of positive and negative electrodes for charge and discharge tests. The constant current charge cut-off voltage is 1.7V, the constant current discharge cut-off voltage is 0.6V, and the current density is 40mA·cm -2, after 100 charge and discharge cycles, the electrolyte coulomb efficiency remained at 96%, the energy efficiency remained at 86%, the voltage efficiency remained at 90%, and the capacity retention rate was 60%. According to the stability test steps of Example 1, after charging, 20 ml of the positive electrode electrolyte was sealed and stored at 40°C, and precipitation occurred after 13 days. 20 ml of the negative electrode electrolyte was sealed under nitrogen protection and stored at 5°C, and precipitation occurred after 6 days.
[0040] Example 4: Preparation of vanadium electrolyte with a total vanadium concentration of 2.10 mol / L, V 3+ and V 4+ The concentration ratio is 1:1, and the proton concentration is 9.0 mol / L. 100 ml of 3# composite additive for vanadium electrolyte is prepared, wherein the first component is composed of 15 g of perfluorobutyl sulfonamide, 5 g of ammonium fluoride, 30 g of ammonium sulfate, and 20 g of phosphoric acid, which are mixed to form a mixture; the second component is composed of 3.5 ml of polyoxyethylene sorbitan monooleate, 3.5 ml of ethanol, and 60 ml of deionized water, which are stirred with a magnetic stirrer for 20 minutes; then the first component and the second component are ultrasonically mixed at room temperature for 20 minutes, stopped, and the volume is fixed to 100 ml with deionized water, and then ultrasonically mixed at room temperature for 10 minutes, and then taken out and sealed for storage. The added volume of 3# composite additive in the positive and negative vanadium electrolytes is 1%. Take the electrolyte for vanadium batteries with equal volumes of positive and negative electrodes for charge and discharge tests. The constant current charge cut-off voltage is 1.7V, the constant current discharge cut-off voltage is 0.6V, and the current density is 40mA·cm -2 , after 100 charge and discharge cycles, the electrolyte coulomb efficiency remained at 96%, the energy efficiency remained at 86%, the voltage efficiency remained at 89%, and the capacity retention rate was 54%. According to the stability test steps of Example 1, after charging, 20 ml of the positive electrode electrolyte was sealed and stored at 40°C, and precipitation occurred after 14 days. 20 ml of the negative electrode electrolyte was sealed under nitrogen protection and stored at 5°C, and precipitation occurred after 6 days.
[0041] Example 5: Preparation of vanadium electrolyte with a total vanadium concentration of 2.10 mol / L, V 3+ and V 4+The concentration ratio is 1:1, and the proton concentration is 9.0 mol / L. 100 ml of 4# composite additive for vanadium electrolyte is prepared, wherein the first component is composed of 30 g of ammonium perfluorobutyl sulfonate, 40 g of ammonium sulfate, and 20 g of phosphoric acid, which are mixed to form a mixture; the second component is composed of 8.0 ml of dehydrated sorbitol ester, 4.0 ml of isopropanol, and 50 ml of deionized water, which are stirred with a magnetic stirrer for 20 minutes; then the first component and the second component are ultrasonically mixed at room temperature for 20 minutes, stopped, and the volume is fixed to 100 ml with deionized water, and then ultrasonically mixed at room temperature for 10 minutes, and then taken out and sealed for storage. The added volume of 4# composite additive in the positive and negative vanadium electrolytes is 1%. Take the electrolyte for vanadium batteries with equal volumes of positive and negative electrodes for charge and discharge tests. The cut-off voltage of constant current charging is 1.7V, the cut-off voltage of constant current discharge is 0.6V, and the current density is 40mA·cm -2 , after 100 charge and discharge cycles, the coulombic efficiency of the electrolyte remained at 96%, the energy efficiency remained at 86%, the voltage efficiency remained at 89%, and the capacity retention rate was 68%. According to the stability experimental steps of Example 1, after charging is completed, 20 ml of the positive electrode electrolyte is sealed and stored at 40°C. Precipitation occurs after 24 days. 20 ml of the negative electrode electrolyte is sealed under nitrogen protection and stored at 5°C. Precipitation occurs after 6 days. The coulombic efficiency, energy efficiency, voltage efficiency and capacity retention rate of the vanadium electrolyte prepared in this example after 100 charge and discharge cycles are as follows Figure 1 shown.
[0042] Comparative Example 1: A single cell experiment was conducted with a vanadium electrolyte, with the positive and negative electrodes having equal volumes and a vanadium concentration of 1.77 mol / L. 3+ and V 4+ The concentration ratio is 1:1 commercial vanadium electrolyte, the diaphragm is Nafion117, and the graphite felt electrode area is 25cm 2 , the current density is 40 mA cm -2 , the charge and discharge voltage range is 0.6-1.7V. The temperature experiment is low temperature 5°C and high temperature 40°C. The mass specific energy is calculated based on the unit mass of vanadium. 100 cycles were carried out at room temperature, the coulomb efficiency was 95%, the energy efficiency was 86%, and the maximum mass specific energy was 0.30Wh / g. After 25 cycles, the capacity retention rate dropped below 90%. According to the stability experimental steps of Example 1, after charging is completed, the negative electrode electrolyte is stabilized at 5°C for 2 days and then crystallizes, and the positive electrode electrolyte is stabilized at 40°C for 2 days and then precipitates.
[0043] Comparative Example 2: Electrolyte was configured for single cell experiment, with positive and negative electrodes of equal volume and vanadium concentration of 1.81 mol / L, V 3+ and V 4+The concentration ratio is 1:1 commercially available electrolyte, the separator is Nafion117, and the graphite felt electrode area is 25cm 2 , the current density is 40 mA cm -2 , the charge and discharge voltage range is 0.6-1.7V. The temperature experiment is low temperature 5℃ and high temperature 40℃. The mass specific energy is calculated based on the unit mass of vanadium. 100 cycles were carried out at room temperature, the coulomb efficiency was 94%, the energy efficiency was 81%, and the maximum mass specific energy was 0.30Wh / g. After 10 cycles, the capacity retention rate dropped below 90%. According to the stability experiment steps of Example 1, after charging is completed, the negative electrode electrolyte is stabilized at 5℃ for 4 days and then crystallizes, and the positive electrode electrolyte is stabilized at 40℃ for 10 days and then precipitates.
[0044] Comparative Example 3: Electrolyte was configured for single cell experiment, with positive and negative electrodes of equal volume and vanadium concentration of 2.10 mol / L, V 3+ and V 4+ The electrolyte without additives in Example 1 with a concentration ratio of 1:1, the separator is Nafion117, and the graphite felt electrode area is 25 cm 2 , the current density is 40 mA cm -2 , the charge and discharge voltage range is 0.6-1.7V. The temperature experiment is low temperature 5℃ and high temperature 40℃. The mass specific energy is calculated based on the unit mass of vanadium. 100 cycles were carried out at room temperature, the coulomb efficiency was 95%, the energy efficiency was 86%, and the maximum mass specific energy was 0.28Wh / g. After 8 cycles, the capacity retention rate dropped below 90%. According to the stability experimental steps of Example 1, after charging is completed, the negative electrode electrolyte is stabilized at 5℃ for 2 days and then crystallizes, and the positive electrode electrolyte is stabilized at 40℃ for 3 days and then precipitates.
[0045] Comparative Example 4: Electrolyte was configured for single cell experiment, with positive and negative electrodes of equal volume and vanadium concentration of 2.10 mol / L, V 3+ and V 4+ The electrolyte containing the 4# additive in Example 5 with a concentration ratio of 1:1, the diaphragm is Nafion117, and the graphite felt electrode area is 25 cm 2 , the current density is 40 mA cm -2 , the charge and discharge voltage range is 0.6-1.7V. The temperature experiment is low temperature 5℃ and high temperature 40℃. The mass specific energy is calculated based on the unit mass of vanadium. 100 cycles were carried out at room temperature, the coulomb efficiency was 96%, the energy efficiency was 86%, and the maximum mass specific energy was 0.30Wh / g. After 23 cycles, the capacity retention rate dropped below 90%. According to the stability experiment steps of Example 1, after charging is completed, the negative electrode electrolyte is stabilized at 5℃ for 6 days and then crystals are precipitated, and the positive electrode electrolyte is stabilized at 40℃ for 24 days and then precipitates.
[0046] The performance data of the vanadium electrolytes of Examples 1-5 are shown in Table 1.
[0047] Table 1 Performance data of vanadium electrolyte
[0048]
[0049] Combining the data in Table 1 and Examples 1-5, it can be seen that compared with the additive-free electrolyte of Example 1, the high-temperature performance of the electrolyte containing composite additives in Examples 2-5 is significantly improved, indicating that the composite additive can effectively improve the stability of the electrolyte. The coulombic efficiency, voltage efficiency and energy efficiency of the five groups of electrolytes in the examples remain stable, with coulombic efficiency at 95%-96%, voltage efficiency at 89%-91%, and energy efficiency at 86%, indicating that the composite additive has little effect on the coulombic efficiency, voltage efficiency and energy efficiency. However, the electrolyte capacity decreases significantly with the accumulation of the number of cycles, but compared with the additive-free electrolyte of Example 1, the capacity retention rate of the electrolyte containing composite additives in Examples 2-5 is significantly improved. The capacity retention rate of the electrolyte containing 4# composite additives in Example 5 is the best after 100 cycles, which is 68%, while the additive-free electrolyte in Example 1 is only 35%.
[0050] Combining the data in Table 2 with Comparative Examples 1-4, it can be seen that Comparative Examples 1 and 2 are both currently commercially available electrolytes, with vanadium concentrations of 1.77 mol / L and 1.81 mol / L, respectively, and Comparative Examples 3 and 4 are both homemade electrolytes of Examples 1 and 5, with a vanadium concentration of 2.10 mol / L. Tested under the same single-cell system, the mass specific energy of the electrolyte without additives in Comparative Example 3 is slightly lower than that of the commercially available electrolytes in Comparative Examples 1 and 2, because the concentration of the electrolyte increases and the solubility decreases, resulting in a decrease in mass specific energy; while the mass specific energy of the electrolyte containing the composite additive in Comparative Example 4 is comparable to the commercially available electrolyte values of Comparative Examples 1 and 2, further illustrating that the composite additive can effectively improve the solubility of high-concentration vanadium electrolysis. In addition, the high and low temperature stability and long cycle stability of the electrolyte containing the composite additive in Comparative Example 4 are better than those of the commercially available electrolytes in Comparative Examples 1 and 2, indicating that the composite additive provided by the present invention is used in high-concentration vanadium electrolytes, which can significantly inhibit the precipitation or crystallization of positive and negative electrode electrolytes, significantly improve the stability of the positive and negative electrode electrolytes, while maintaining the electrochemical activity at high concentrations and reducing battery capacity attenuation.
[0051] Table 2 Performance data of homemade vanadium electrolyte and commercially available vanadium electrolyte
[0052]
[0053] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0054] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A composite additive for vanadium electrolyte, characterized in that: Applicable to the electrolyte of vanadium battery, the electrolyte is positive electrode electrolyte and negative electrode electrolyte, the composite additive comprises: A mixture formed by a first component and a second component, wherein the first component includes at least one of a fluorine-containing compound, an oxygen-containing acid and an oxygen-containing acid salt, and the second component is a surfactant.
2. The composite additive according to claim 1, characterized in that: The first component includes at least one of potassium perfluorobutyl sulfonate, perfluorobutyl sulfonyl fluoride, perfluorobutyl sulfonamide, ammonium perfluorobutyl sulfonate, ammonium fluoride, ammonium hydrogen fluoride, ammonium sulfate, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid and sulfuric acid.
3. The composite additive according to claim 1, characterized in that: The second component includes: an aqueous solution formed by at least one of polyoxyethylene esters, sorbitan esters, glycerol fatty acid esters, alkyl phosphates, ethanol, ethylene glycol, isopropanol, propylene glycol, and glycerol.
4. The composite additive according to claim 1, characterized in that: The mass concentration of the second component in the composite additive is 4%-10%.
5. The composite additive according to claim 1, characterized in that: The added amount of the composite additive is 0.5%-2% of the volume of the electrolyte.
6. The composite additive according to claim 1, characterized in that: The vanadium ion concentration in the electrolyte is 1.7-3.0 mol / L.
7. The composite additive according to claim 1, characterized in that: The proton concentration of the electrolyte supporting electrolyte is 8.0-10.0 mol / L.
8. The composite additive according to claim 1, characterized in that: The electrolyte V 3+ and V 4+ The concentration ratio is 1:
1.
9. A method for preparing a composite additive for vanadium electrolyte, characterized in that: Used for preparing the composite additive for vanadium electrolyte according to any one of claims 1 to 8, the method comprising: The mixture is prepared by adding 150-850 g of the first component to each liter of the second component and mixing; Wherein, the first component comprises: at least one of a fluorine-containing compound, an oxygen-containing acid and an oxygen-containing acid salt, and the second component is a surfactant.
Citation Information
Cited By
Composition for promoting continuous production of vanadium electrolyte and application thereof
CN120978101A
Positive electrode electrolyte additive of all-vanadium redox flow battery, preparation method of positive electrode electrolyte additive, positive electrode electrolyte and application of positive electrode electrolyte additive
CN121215821A